Satyāgrahanī saptapadī : satyāgrahanī sāta ladatono itihāsa - Desāī, Maganabhāī Prabhudāsa (SAMP early 20th-century Indian books project, 1952)
Essays on seven movement in the history of Indian freedom struggle.